Jordan's current account behavior: a structural break approach to consumption-smoothing analysis - Abdalla, Khawlah A., author; Ozawa, Terutomo, advisor; Davies, Stephen P., advisor; Phillips, Ronnie J., committee member; Kling, Robert, committee member (Colorado State University. Libraries, 2005)
In recent years the current account behavior has been taken on much concern. The intertemporal approach to the current account is one of the models that tried to explain this behavior and its implications. The imbalances in the current account are interpreted as a sign of disequilibrium in international relations. Jordan as one of the developing countries has suffered from a severe current account imbalances. This study tried to understand the variability of Jordan's current account implying the consumption-smoothing approach with utilizing the structural break model. Structural change has been one of the major anxieties in economics. Different theories on phases of economic development and growth postulate that an economic relationship changes over time. This dissertation explored the Jordanian current account behavior during the period of 1967-2002. The intertemporal consumption-smoothing approach to the determination of the current account implies that international capital flows act as a buffer to smooth aggregate consumption in the face of temporary shocks in the economic fundamentals (output, investment, and government spending). The Jordanian current account has been examined empirically using the intertemporal approach to know whether the movement of the current account follows the optimizing behavior. Using the Gregory and Hansen (1996) residual-based tests for cointegration in models with regime shifts, we get two sub-periods, which represent a potential behavior change between the current account variables. The study evaluated the solvency condition for Jordan's current account, the degree of optimality of the intertemporal consumption-smoothing through current account, and whether its international financial capital flows have been optimal. The study also estimates the optimal consumption-smoothing component for Jordan's current account based on an intertemporal optimization model for the two sub-periods and carries out a hypothesis test to evaluate the performance of the model. According to the result, the actual consumption-smoothing of Jordan's current account was consistent with optimal smoothing for the later sub-period but not for the earlier one. It also has explained the major structural changes and policies that characterized the period of the study. Moreover, the dissertation tried to suggest policy measures to smooth out the balance of payments disequilibrium.
Keywords: finance; studies